Climate crisis and environmental sustainability perspective of 11,000 scientists - Escobar-Mamani, Fortunato (2019)
It is evident the environmental crisis and consequently the global climate crisis in the current convergence, caused by the crisis of civilization, which privileges the exploitation of natural resources based on the economic, ecological and cultural model that favors more power groups or the so-called dominant societies linked to the excessive consumption of the lifestyles of developed countries and their agents. Its consequences, are adverse to the point of its real collapse, induces an obvious danger not only for human health, but also for the health of the same nature, which covers the current civilization. It is possible that everyone is responsible, one more than others, is a matter of debate. Within this perspective, in the last issue of the year (2019) of the Journal of High Andean Research (RIA) we find it convenient to include (replicate) manifest of "11,000 scientists who warn of the consequences of the climate crisis"; The purpose is to provoke the debate on the positions of scientists to try to understand the causes, effects and their possible solutions from various territorial spaces of the global world, that collect the other knowledge, even if asleep, refloat them as personal and social heritage. Bearing in mind that the current climate plans and the socio-environmental strategies of developed countries so far are not the most "adequate". For the aforementioned, we transcribe in the following lines the recently published document and base them, invite our readers and all those involved could send their manuscripts on socio-environmental issues as part of the RIA research lines to support the socio-substantive environmental and contribute to the achievement of the sustainable development goals of the 2030 diary (17 Objectives and 169 goals) of the Organization of Nations, which must be part of proposals for environmental public policies towards higher levels of efficiency and justice environmental.